Zanubrutinib or Ibrutinib in Relapsed or Refractory Chronic Lymphocytic Leukemia - Brown, Jennifer R; Eichhorst, Barbara; Hillmen, Peter; Jurczak, Wojciech; Kaźmierczak, Maciej; Lamanna, Nicole; O'Brien, Susan M; Tam, Constantine S; Qiu, Lugui; Zhou, Keshu; Simkovic, Martin; Mayer, Jiri; et al. (The New England journal of medicine, 2023)
BACKGROUND: In a multinational, phase 3, head-to-head trial, ibrutinib, a Bruton's tyrosine kinase (BTK) inhibitor, was compared with zanubrutinib, a BTK inhibitor with greater specificity, as treatment for relapsed or refractory chronic lymphocytic leukemia (CLL) or small lymphocytic lymphoma (SLL). In prespecified interim analyses, zanubrutinib was superior to ibrutinib with respect to overall response (the primary end point). Data from the final analysis of progression-free survival are now available. METHODS: We randomly assigned, in a 1:1 ratio, patients with relapsed or refractory CLL or SLL who had received at least one previous course of therapy to receive zanubrutinib or ibrutinib until the occurrence of disease progression or unacceptable toxic effects. In this final analysis, progression-free survival (a key secondary end point) was assessed with the use of a hierarchical testing strategy to determine whether zanubrutinib was noninferior to ibrutinib. If noninferiority was established, the superiority of zanubrutinib was assessed and claimed if the two-sided P value was less than 0.05. RESULTS: At a median follow-up of 29.6 months, zanubrutinib was found to be superior to ibrutinib with respect to progression-free survival among 652 patients (hazard ratio for disease progression or death, 0.65; 95% confidence interval, [CI], 0.49 to 0.86; P = 0.002), as assessed by the investigators; the results were similar to those as assessed by an independent-review committee. At 24 months, the investigator-assessed rates of progression-free survival were 78.4% in the zanubrutinib group and 65.9% in the ibrutinib group. Among patients with a 17p deletion, a TP53 mutation, or both, those who received zanubrutinib had longer progression-free survival than those who received ibrutinib (hazard ratio for disease progression or death, 0.53; 95% CI, 0.31 to 0.88); progression-free survival across other major subgroups consistently favored zanubrutinib. The percentage of patients with an overall response was higher in the zanubrutinib group than in the ibrutinib group. The safety profile of zanubrutinib was better than that of ibrutinib, with fewer adverse events leading to treatment discontinuation and fewer cardiac events, including fewer cardiac events leading to treatment discontinuation or death. CONCLUSIONS: In patients with relapsed or refractory CLL or SLL, progression-free survival was significantly longer among patients who received zanubrutinib than among those who received ibrutinib, and zanubrutinib was associated with fewer cardiac adverse events. (Funded by BeiGene; ALPINE ClinicalTrials.gov number, NCT03734016.).
Keywords: Antineoplastic Agents; Disease Progression; lidé; chronická lymfatická leukemie; progrese nemoci; protinádorové látky; Heart Diseases; Humans; nemoci srdce; Leukemia, Lymphocytic, Chronic, B-Cell